Osmotic and air drying of lacatan and saba bananas - Deada, Maximina B.; Arcellana, Mayi Y. (1968.)
Osmotic and air drying of Lacatan and Saba bananas in refined, dry cane sugar and in 70% sugar syrup showed that Lacatan exhibited greater weight loss than Saba during the two-stage dehydration process. A lower final moisture content and a higher total sugar were noticed for dried Lacatan than for dried Saba. Similarly dry sugar proved effective in promoting greater water removal than the syrup but it had the tendency to crystallize on the fruit's surface. Rank analysis of the subjective evaluation gave not much significant differences among the samples with regard to color, flavor and texture.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bananas -- Varieties; Bananas